Bone cell differentiation and mineralization in wild-type and osteogenesis imperfecta zebrafish are compromised by per- and poly-fluoroalkyl substances (PFAS) - Francesca Tonelli; Cecilia Masiero; Carla Aresi; Camilla Torriani; Simona Villani; Guido Premoli; Antonio Rossi; Antonella Forlino (Scientific Reports)
Abstract Perfluorinated compounds (PFAS) are well recognized toxic pollutants for humans, but if their effect is equally harmful for healthy and fragile people is unknown. Addressing this question represents a need for ensuring global health and wellbeing to all individuals in a world facing the progressive increase of aging and aging related diseases. This study aimed to evaluate the impact of perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA) and perfluorohexanoic acid (PFHxA) exposure on development and skeletal phenotype using the osteogenesis imperfecta (OI) zebrafish model Chihuahua (Chi/+), carrying a dominant glycine substitution in the α1 chain of collagen I and their wild-type (WT) littermates. To this purpose Chi/+ and WT zebrafish expressing the green fluorescent protein under the early osteoblast marker osterix were exposed from 1 to 6 days post fertilization to 0.36, 1.5 and 3.0 mg/L PFOS, 0.005 and 0.5 mg/L PFOA and 0.01, 0.48 and 16.0 mg/L PFHxA, and their development and skeletal phenotype investigated. Morphometric measurements, confocal microscopy evaluation of operculum area delimited by the fluorescent preosteoblasts and mineral deposition analysis following alizarin red staining were employed. PFOS and the highest concentration of PFHxA significantly impaired standard length in both genotypes. Osteoblast differentiation was significantly compromised by PFOS and by PFOA only in Chi/+. Limited to WT exposed to PFOA a reduced mineralization was also observed. No effect was detected after PFHxA exposure. Apoptosis was only activated by PFOA, specifically in Chi/+ mutant operculum osteoblasts. Interestingly, an altered lipid distribution in both WT and mutant fish was revealed after exposure to both pollutants. In conclusion, our data demonstrate that PFAS impair operculum development mainly compromising cell differentiation in mutant fish whereas alter lipid hepatic distribution in both genotypes with a more severe effect on Chi/+ preosteoblast survival. These results represent a first warning sign of the negative impact of PFAS exposure in presence of genetically determined skeletal fragility.